Pengembangan LKPD Berbasis Masalah Bilangan Cacah Dengan Konteks Pasar Terapung Siring Menara Pandang SD/MI - Oktavia, Ela; Karim, Karim; Suryaningsih, Yuni (Mandalika Mathematics and Educations Journal, 2025)
Mathematics plays a crucial role in daily life, and understanding basic mathematical concepts such as whole numbers is vital for students in developing problem-solving skills. Additionally, students can gain an understanding of and appreciation for the cultural values present in their community. By integrating student worksheets that are linked to culture, especially the Banjar Floating Market Culture, it is hoped that students will become more aware of the cultural elements in their surroundings. Therefore, the aim of this study is to create a problem-based student worksheets focused on whole numbers with the context of the Siring Menara Pandang Floating Market for fourth grade elementary school students that is valid, practical, and effective. The research methodology employed is Research and Development (R&D), utilizing the ADDIE framework for the development process. The research instruments applied include validation sheets, student response questionnaires, and evaluation tests. Validity testing was conducted by three validators, consisting of two teachers and one university lecturer. Practicality testing was carried out through student response questionnaires, while effectiveness was determined based on the results of evaluation tests. The validity test yielded a score of 3.61, categorized as highly valid. The student response questionnaires returned a score of 3.71, classified as highly practical. The evaluation test results showed an 85% success rate, categorized as effective. Based on these findings, it can be concluded that the problem-based student worksheets on whole numbers for fourth grade elementary school students is deemed valid, practical, and effectiveI